Diagnostic accuracy of Abbott Architect Assay as a screening tool for human T‐cell leukaemia virus type‐1 and type‐2 infection in a London teaching hospital with a large solid organ transplant centre. Issue 3 (26th April 2022) - Lee, Nathaniel; Murphy, Jamie; Al‐Khudairi, Rasheed; Sturdy, Ann; Mahungu, Tabitha; Haque, Tanzina; Griffiths, Paul; Tosswill, Jennifer; Irish, Dianne
Abstract: Aim: In the United Kingdom, organ donors/recipients are screened for evidence of human T‐cell leukaemia virus type‐1 and type‐2 (HTLV‐1/2) infections. Since the United Kingdom is a low prevalence country for HTLV infections, a screening assay with high sensitivity and specificity is required. Samples with repeat reactivity on antibody testing are sent to a reference lab for confirmatory serological and molecular testing. In the case of donor screen, this leads to delays in the release of organs and can result in wastage. We aim to assess whether a signal/cut‐off (S/CO) ratio higher than the manufacturer's recommendation of 1.0 in the Abbott Architect antibody assay is a reliable measure of HTLV‐1/2 infection. Methods: We conducted a 5 year retrospective analysis of 7245 patients from which 11 766 samples were tested on the Abbott Architect rHTLV I/II assay. Reactive samples (S/CO >1) were referred for confirmatory serological and molecular detection (Western Blot and proviral DNA) at UK Health Security Agency, (formerly PHE, Colindale), the national reference laboratory. Electronic, protected laboratory and hospital patient databases were employed to collate data. Results: A total of 45 patients had initially reactive samples. 42.2% ( n =  19/45) had an S/CO ratio > 20, with HTLV infection confirmed in n =  18/19 and indeterminate confirmatory results in n =  1/19. No samples with an S/CO ratio <4 (48.9%, n =  22/45) or 4–20 (8.9%, n =  4/45) had positive confirmatory results on subsequent confirmatory testing. Conclusion: Samples with an S/CO >20 likely represent a true HTLV‐1/2 infection. Reactive samples with an S/CO <4 were unlikely to confirm for HTLV infections. Interpretation of these ratios can assist clinicians in the assessment of low reactive samples and reiterates the need for faster access to confirmatory testing.